2022
DOI: 10.1007/s11442-022-1990-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of sea-island prehistoric dune sites, Holocene sea levels, and aeolian sand activities in Fujian Province, China

Abstract: The lower reaches of the Minjiang River and its adjacent areas were among the most active prehistoric archaeological areas in Fujian Province. The accumulation types of Neolithic archaeological strata are roughly divided into dune sites and dune/shell mound sites. The sites can also be roughly divided into estuarine, coastal, and sea-island sites based on their geomorphic features. The cultural development of these prehistoric sites is of great significance for understanding the migration and spread of Austron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The decay curve shows that the signal rapidly reached the background value after 1 s of OSL stimulation. An F R value of 110 indicates that the fast component is responsible for most of the signal in the first channel (Jin et al, 2022). Furthermore, the component fitting result (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The decay curve shows that the signal rapidly reached the background value after 1 s of OSL stimulation. An F R value of 110 indicates that the fast component is responsible for most of the signal in the first channel (Jin et al, 2022). Furthermore, the component fitting result (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pingtan Island is located at the northeast terminus of the Changle-Zhao'an active fault belt, and the rock outcrop is mainly of igneous origin from the late Yanshanian. Approximately 66% of the total island area is covered by aeolian sand, contributing to the formation of a typical coastal aeolian geomorphic landscape in southern China [25].…”
Section: Topography and Geomorphologymentioning
confidence: 99%
“…Layer 6 is characterised by red fine aeolian sand and clay, chunky shell accumulation (Figure 2d) and several pieces of fragmented pottery (Figure 2g). From the point of view of the accumulation types of Neolithic archaeological strata, the JH site is a dune/shell mound site (Jin et al, 2022). The shellfish remains found so far are mainly two species: Arca granosa and Metrix lusoria (Figure 2f), which inhabit intertidal zones or sandy muddy seafloor in shallow seas.…”
Section: Study Area and Site Descriptionmentioning
confidence: 99%
“…According to the available data and statistics, the Neolithic sites of 7-5 ka BP in Haitan Island were all laid out on terraces 10 m above contemporary sea levels, which were formed by the accumulation of Old Red Sand or granite weathered shells from the late Pleistocene to the early Holocene; this is in agreement with the small-scale geomorphological living environment of the JH site in this study. In terms of cultural inheritance type, the JH site is classified as the second type of single type site in the context of high sea surface (Jin et al, 2022), and there is no follow-up palaeoanthropogenic activity after the Keqiutou culture. By examining the relationship between the sea surface changes and the number of sites in the corresponding period, we found that the spatial distribution range of ancient humans expanded to the southern end of Haitan Island during the relatively high sea level period and increased in numbers, such as the Keqiutou and Huangtulun culture periods.…”
Section: Regional Environmental Change and Ancient Human Activities O...mentioning
confidence: 99%
See 1 more Smart Citation